2014
DOI: 10.1111/sbr.12040
|View full text |Cite
|
Sign up to set email alerts
|

Excessive daytime sleepiness among pregnant women: An epidemiological study

Abstract: The aim of the present study was to clarify the prevalence of excessive daytime sleepiness and its associated factors among pregnant women in Japan. Of the 940 randomly selected survey locations identified by the Japan Association of Obstetricians and Gynecologists, 344 obstetric institutions participated in the survey. The study was conducted on women with confirmed pregnancies who had had a second or subsequent consultation at one of these institutions. The survey items included age, highest educational achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Additionally, women in their third trimester of pregnancy showed an increased prevalence of excessive sleep duration during pregnancy. A previous study conducted in Japan showed that excessive daytime sleepiness was significantly higher in an earlier trimester of pregnancy [ 18 ]. Almost all Chinese pregnant women with jobs were on maternity leave in the third trimester of pregnancy and, thus, they were more likely to have time to sleep longer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, women in their third trimester of pregnancy showed an increased prevalence of excessive sleep duration during pregnancy. A previous study conducted in Japan showed that excessive daytime sleepiness was significantly higher in an earlier trimester of pregnancy [ 18 ]. Almost all Chinese pregnant women with jobs were on maternity leave in the third trimester of pregnancy and, thus, they were more likely to have time to sleep longer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that age and marital status [ 14 ], low socioeconomic status [ 15 ], employment during pregnancy [ 16 ], number of pregnancies [ 17 ], trimester of pregnancy [ 18 ], passive smoking [ 19 ], and smoking and drinking [ 20 ], are associated with sleep duration among pregnant women. Previous studies showed that poor sleep quality was associated with various factors, including age [ 14 ], low socioeconomic status [ 15 ], at later stage of pregnancy [ 21 ], higher education [ 22 ], residence [ 7 ], minorities [ 23 ], and parity [ 24 ], smoking and drinking [ 20 ], sleeping duration of less than 7 h [ 25 ] among pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on sleep disturbances during pregnancy have been conducted. In an epidemiological survey conducted in 2014, excessive daytime sleepiness was reported in 6.2% of pregnant women, especially among those who were younger and working full-time [4]; the survey also clari ed that pregnant women with sleep-related problems such as alcohol drinking, restless sleep, snoring, apnea, and restless leg syndrome also experienced excessive daytime sleepiness. In another survey, it was estimated that 10-46% of pregnant women started snoring after the second trimester of pregnancy; additionally, the incidence of snoring increased from approximately 11% in the rst trimester of pregnancy to 25% in the third trimester [5].…”
Section: Introductionmentioning
confidence: 99%
“…1 Average number of physical activities: average number of physical activities per minute2 Total sleep time: sum of time determined as sleep3 Sleep e ciency: percentage of total sleep time in the time period from falling asleep to waking up4 Wake after sleep onset: total wake time in the time period from falling asleep to waking up5 Sleep latency: time from beginning of formal time period to falling asleep (sleep of 20 minutes or more) VAS: visual analog scale (1-100, not feeling refreshed-feeling refreshed) PSQI-J, Pittsburgh Sleep Quality Index-Japanese version [table3Near Here]…”
mentioning
confidence: 99%